2021
DOI: 10.4317/jced.57660
|View full text |Cite
|
Sign up to set email alerts
|

Management of dental anxiety via distraction technique

Abstract: Background The purpose of this study was to evaluate the use of a stress ball as a distraction technique on stress levels of patients undergoing a dental procedure. Material and Methods A randomized, split-mouth design was conducted using 20 adult subjects requiring scaling and root planing (Sc/RP) in all four quadrants. Each side of the mouth (maxillary/mandibular) received Sc/RP with local anesthetic with or without the use of a stress-ball distraction over two separa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…Many of the interventions designed to address DFA in children, such as modeling or distraction techniques, have limited evidence to support their use [ 15 , 28 , 235 , 236 ]. Research findings examining distraction and modeling techniques are mixed, with some studies reporting a decrease in DFA, whereas others found either mixed results or no difference (e.g., [ 237 , 238 , 239 , 240 , 241 , 242 , 243 , 244 , 245 , 246 , 247 , 248 , 249 , 250 , 251 , 252 , 253 , 254 ]). Tell–show–do, one of the most popular techniques utilized by dentists, likewise has little evidence to support its efficacy; however, it is widely accepted by children and parents, and there are no contraindications for its use [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Many of the interventions designed to address DFA in children, such as modeling or distraction techniques, have limited evidence to support their use [ 15 , 28 , 235 , 236 ]. Research findings examining distraction and modeling techniques are mixed, with some studies reporting a decrease in DFA, whereas others found either mixed results or no difference (e.g., [ 237 , 238 , 239 , 240 , 241 , 242 , 243 , 244 , 245 , 246 , 247 , 248 , 249 , 250 , 251 , 252 , 253 , 254 ]). Tell–show–do, one of the most popular techniques utilized by dentists, likewise has little evidence to support its efficacy; however, it is widely accepted by children and parents, and there are no contraindications for its use [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…In another study, anxiety after cystoscopy was also significantly lower in the stress ball group than in the control group (Gezginci, Iyigun, Kibar, et al, 2018). However, in their study of stress balls used in the management of dental anxiety, Torres-Gomez, Arnason, Hoopes, and Vandewalle (2021) observed no significant difference in anxiety scores between patients who did and did not use a stress ball. Similarly, in another study examining the effect of distraction methods during lithotripsy, no significant difference was found between the stress ball and control group in terms of anxiety levels (Gezginci, Iyigun, Yalcin, et al, 2018).…”
Section: Discussionmentioning
confidence: 93%
“…sedated endoscopy is done by administering sedative agents to the patient during endoscopy (Obara et al, 2015;teh, shabbir, yuen, & so, 2020). However, performing endoscopy under sedation can lead to many complications.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Particularly, psychophysiological variables are gaining interest in the assessment of stress and burnout in the field of occupational medicine ( De Looff et al, 2018 ). Recent findings in Dentistry suggest that they can also supply information to assess dental anxiety in patients ( Drury and Simonetti, 2019 ; Košir et al, 2021 ; Torres-Gomez et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%